PENGARUH CITRA MERK TERHADAP LOYALITAS PELANGGAN PRODUK SARI ROTI PADA PT NIPPON INDOSARI CORPINDO PEKANBARU - Harwina, Yulia (Eko dan Bisnis: Riau Economic and Business Review, 2022)
This study aims to determine the effect of brand image on the effect of brand image on customer loyalty of Sari Roti products at PT Nippon Indosari CorpindoPekanbaru. In this study the data were collected through a questionnaire to 71 respondents. Then performed an analysis of the data obtained in the form of quantitative analysis. The results of data processing showed that the hypothesis testing with the t test, there is a t count of 11.018 and a t table of 1.994 and this means t count 11.018> t table = 1.994 which means that brand image has a significant effect on customer loyalty of Sari Roti products at PT Nippon Indosari Corpindo Pekanbaru. The regression equation Y = a + bX is Y = 9,452 + 0.801 X, the constant (a) is 9,452, meaning that when the brand image is not taken into account or zero, then customerloyalty is still obtained at 9,452. Meanwhile, the effect of brand image on customer loyalty of Sari Roti products at PT Nippon Indosari Corpindo Pekanbaru is positive as evidenced by the results of the regression coefficient (b) of 0.801, which means that each one unit brand image improvement will increase customer loyalty by 0.801 units. The value of R Square is 0.638. This means that the contribution of the influence of thebrand image on customer loyalty of Sari Roti products at PT Nippon Indosari Corpindo Pekanbaru is 63.80%